The cross from a distance atonement in Mark's gospel - Bolt, Peter G. 1958- (Leicester, UK IVP, 2004)
Inlcudes bibliographical references and indexes.
Keywords: Bible. N.T. Mark -- criticism, interpretation, etc; Atonement (theology).